2016
DOI: 10.1007/s00424-016-1858-x
|View full text |Cite
|
Sign up to set email alerts
|

Klotho modulates FGF23-mediated NO synthesis and oxidative stress in human coronary artery endothelial cells

Abstract: Chronic kidney disease (CKD) is a state of Klotho deficiency and excess of the phosphaturic hormone fibroblast growth factor 23 (FGF23). Both dysregulations were shown to be associated with endothelial dysfunction in humans, but direct vascular effects of FGF23 remain largely elusive. In vitro experiments were performed to assess the effects of FGF23 (10 ng/mL) in relation to its co-receptor Klotho on nitric oxide (NO) synthesis and reactive oxygen species (ROS) formation and detoxification in human coronary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 62 publications
4
71
2
1
Order By: Relevance
“…A recent in vitro study using cultured human coronary artery endothelial cells demonstrated that, in the presence of klotho, FGF23 induces NO release and its stimulating effects on oxidative stress are counterbalanced by increased reactive oxygen degradation [57]. This may at least partly explain the lack of association between endothelial function and FGF23 levels in the present study, as sklotho levels were normal in the majority of our patients.…”
Section: Discussioncontrasting
confidence: 46%
“…A recent in vitro study using cultured human coronary artery endothelial cells demonstrated that, in the presence of klotho, FGF23 induces NO release and its stimulating effects on oxidative stress are counterbalanced by increased reactive oxygen degradation [57]. This may at least partly explain the lack of association between endothelial function and FGF23 levels in the present study, as sklotho levels were normal in the majority of our patients.…”
Section: Discussioncontrasting
confidence: 46%
“…Basic research studies have demonstrated that FGF23 induces the onset and development of atherosclerosis through its effects on vascular calcification and endothelial dysfunction [7, 8]. Recently, clinical studies provided evidence supporting the relationship between increased circulating FGF23 levels and atherosclerotic cardiovascular disease [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Richter et al . utilized coronary artery ECs to highlight that in states of α-Klotho deficiency, FGF-23 mediated NO production is attenuated, leading to an increase of reactive oxygen species (ROS) [22]. Two recent studies also showed that α-Klotho expression in human ECs declined under uremic status and with cell aging, which might account for vascular dysfunction under these conditions [23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…As stated recently, Richter et al ., using human coronary artery ECs, also showed that NO production increases after FGF-23 treatment and this was dependent on the presence of α-Klotho [22]; however, their results suggest that these effects are due to the secretion of the soluble α-Klotho. In contrast, our study highlights that the addition of soluble α-Klotho to HAECs following α-Klotho knockdown was unable to rescue EC resistance to FGF-23.…”
Section: Discussionmentioning
confidence: 99%